METODE MAJELIS ULAMA INDONESIA (MUI) DALAM PENGAWASAN DAN PEMBINAAN ALIRAN KEAGAMAAN DI KABUPATEN SELUMA - Aidi Muksin (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: The background of this research on the method of the Indonesian Ulema Council (MUI) in the guidance and supervision of religious sect in Seluma. This study uses qualitative research methods to understand the phenomenon of what is experienced by research subjects. Data collection techniques used were interviews, observation and documentation. The usefulness of this study to determine the strategy of the clergy Indonesia (MUI) in coaching religious sect in Seluma. These results indicate that the method of the Indonesian Ulema Council Seluma in supervising and coaching the development of religious beliefs, which heretical, after the authors analyzed data that had writers in the field can get the authors conclude that the Indonesian Ulema Council Seluma have a good strategy in anticipation of the growing cult. Indonesian Ulema Council Seluma have a clear program and running properly, exercise direct supervision of the study groups that exist in Seluma conduct control directly or indirectly the process of learning and books are taught in school, the board is very controlling institutions da’wah Seluma, socialize orally about the criteria the religious to the community, socialize criteria heretical sects through books and bulletins, conduct a seminar on Islamic teachings, controlling directly pratek shamanic society, have data on the cult and spreading, making the community as a partner and in the line of duty, when the Indonesian Ulema Council Seluma received reports from the public both groups and individuals about the existence of a cult environment of citizens of the Indonesian Ulema Council Seluma immediately held observation to further investigate if it is true then the Majelis Ulama Indonesia Seluma advises leadership and encourage the flow back to the beaten path, if they do not want it to be handed over to the law enforcement authorities. The authors conclude that the board of the Indonesian Ulema Council Seluma own srtategi well in anticipation of the development of heretical sects but not maximized. In the implementation of the Indonesian Ulema Council committee Seluma also carry out their duties by the Qur’an and the Sunnah of the Prophet the board of the Indonesian Ulema Council has full responsibility to anticipate the growth of religious denominations and passed a fatwa to Muslims.